Randomised trial of a mobile coronary care unit for emergency calls. Issue 6120 (29th April 1978) - Hampton, J R; Nicholas, C
Abstract : A randomised trial was conducted to assess the value of sending a mobile coronary care unit (MCCU) to all emergency calls other than those for children or for patients injured in road-traffic accidents or brawls. Over 15 months 6223 calls for emergency ambulances were considered for the study, but a routine ambulance had to be dispatched on 2583 occasions because the MCCU was not available. A group of 1664 patients was randomly allocated to transport by the MCCU and 1676 patients to routine transport. In these groups the prehospital mortality among patients with heart attacks was 45% and 47%, and no patient survived resuscitation attempts long enough to leave hospital. During the same period general practitioners sent 190 patients with heart attacks to hospital in routine ambulances and none of them died during the interval between the call for the ambulance and arrival at hospital. Although it may be worth equipping all emergency ambulances with a defibrillator, MCCUs as at present envisaged will not appreciably affect mortality from heart attacks.